Predictive Policing: The Role of Crime Forecasting in Law Enforcement Operations - Walter L. Perry, Brian McInnis, Carter C. Price, Susan C. Smith, John S. Hollywood (RAND Corporation, 2013)
Smart, effective, and proactive policing is clearly preferable to simply reacting to criminal acts. Although there are many methods to help police respond to crime and conduct investigations more effectively, predicting where and when a crime is likely to occur—and who is likely responsible for prior crimes—has recently gained considerable currency. Law enforcement agencies across the United States are employing a range of predictive policing approaches, and much has been written about their effectiveness. This guide for practitioners offers a focused examination of the predictive techniques currently in use, identifies the techniques that show promise if adopted in conjunction with other policing methods, and shares findings and recommendations to inform future research and clarify the policy implications of predictive policing. This work was sponsored by the National Law Enforcement and Corrections Technology Center of Excellence on Information and Geospatial Technology at the National Institute of Justice (NIJ). This guide will be of interest to law enforcement personnel at all levels and is one in a series of NIJ-sponsored resources for police departments. The research reported here was conducted in the RAND Safety and Justice Program, which addresses all aspects of public safety and the criminal justice system, including violence, policing, corrections, courts and criminal law, substance abuse, occupational safety, and public integrity. Program research is supported by government agencies, foundations, and the private sector. This program is part of RAND Justice, Infrastructure, and Environment, a division of the RAND Corporation dedicated to improving policy and decisionmaking in a wide range of policy domains, including civil and criminal justice, infrastructure protection and homeland security, transportation and energy policy, and environmental and natural resource policy.